Statistics for research - Dowdy, S. M.; Chilko, Daniel M.; Wearden, Stanley, 1926-; John Wiley & Sons.; Wiley InterScience (Online service) (Hoboken, NJ : Wiley-Interscience, 2004)
'The text features the most commonly used statistical techniques for the analysis of research data. As in the earlier editions, emphasis is placed on how to select the proper statistical procedure and how to interpret results. Whenever possible, to avoid using the computer as a'black box' that performs a mysterious process on the data, actual computational procedures are also given.''A must for scientists who analyze data, professionals and researchers who need a self-teaching text, and graduate students in statistical methods, Statistics for Research, Third Edition brings the methodology up to date in a very practical and accessible way.'--Jacket.
1. The Role of Statistics -- 2. Populations, Samples, and Probability Distributions -- 3. Binomial Distributions -- 4. Poisson Distributions -- 5. Chi-Square Distributions -- 6. Sampling Distribution of Averages -- 7. Normal Distributions -- 8. Student's t Distribution -- 9. Distributions of Two Variables -- 10. Techniques for One-way Analysis of Variance -- 11. The Analysis-of-Variance Model -- 12. Other Analysis-of-Variance Designs -- 13. Analysis of Covariance -- 14. Multiple Regression and Correlation.
Includes bibliographical references and index.
Print version record.
Keywords: Mathematical statistics; Statistics; Statistique mathématique.; Applied Probability and Statistics; FACsci; ER -- Internet -- Book -- Full text; Electronic books